Integrated transcriptome analysis of immune-related mRNAs and microRNAs in Macrobrachium rosenbergii infected with Spiroplasma eriocheiris. Issue 119 (December 2021) - Ou, Jiangtao; Chen, Hao; Liu, Qiao; Bian, Yunxia; Luan, Xiaoqi; Jiang, Qicheng; Ji, Hao; Wang, Zisheng; Lv, Linlan; Dong, Xuexing; Zhao, Weihong; Zhang, Qihuan
Abstract: Macrobrachium rosenbergii ( M. rosenbergii ), is a major aquaculture species in China and Southeast Asia. However, infection with Spiroplasma eriocheiris (S. eriocheiris) has caused huge economic losses to the cultivation of M. rosenbergii . Currently, there are few reports on the immune response mechanism of M. rosenbergii that are infected with S. eriocheiris . To clarify the immune response mechanism of M. rosenbergii infected with S. eriocheiris, the key immune genes which respond to the infection with the pathogen and the regulation of related microRNAs (miRNAs) on them were identified. In this study, the mRNA and miRNA transcriptome of hepatopancreas of M. rosenbergii at different infection stages were analyzed using high-throughput sequencing and qRT-PCR. In the mRNA transcriptome, 27, 703 and 33, 402 genes were expressed in healthy and susceptible M. rosenbergii, respectively. By digital gene-expression profiling analysis, 23, 929 and 24, 325 genes were expressed, and 223 and 373 genes were significantly up-regulated and down-regulated, respectively. A total of 145 key genes related to Toll, IMD, JAK/STAT and MAPK were excavated from the transcriptome. In the miRNA transcriptome, 549 miRNAs (Conserved : 41, PN-type: 83, PC-type: 425) were sequenced, of which 87 were significantly up-regulated and 23 were significantly down-regulated. Among the related immune pathways, there are 259 miRNAs involved in the regulation of target genes in the Toll and IMD pathways, 231 JAK/STAT pathways and 122 MAPK pathways. qRT-PCR differential detection of immune-related miRNAs and mRNAs showed that 22 miRNAs with significant differences (P < 0.05) such as mro-miR-100, PC-mro-3p-27 and PN-mro-miR-316 had corresponding regulatory relationships with 22 important immune genes such as TLR2, TLR3, TLR4, TLR5, MyD88, Pelle and Relish in different stages after infection. In this study, the immune genes and related regulatory miRNAs of M. rosenbergii in response to S. eriocheiris infection were obtained. The results can provide basic data to further reveal the immune defense mechanism of M. rosenbergii against S. eriocheiris infection. Highlights: Comprehensive transcriptome profiling of M. rosenbergii challenged with S. eriocheiris . 145 key genes related to Toll, IMD, JAK/STAT and MAPK were excavated. A total of 549 miRNAs, of which 87 were significantly up-regulated and 23 were significantly down-regulated. QRT-PCR differential detection for 22 immune-related miRNAs and mRNAs, respectively.